A Bio-economic Study of the Trophic Structure of the Omani Fish Catch - Medhat Abd El-Barr Abd El-Rahman (Tropical Life Sciences Research, 2014)
The present study was conducted to obtain estimates of certain biological and economic indices of the trophic structure of the Omani landed fish catch, namely, the mean trophic level (MTL), the fishing-in-balance (FiB) index and the relative price index (RPI). The MTL generally decreased from 1995 to 2010, indicating a fishing-down of the marine trophic web. The FiB index increased, indicating an imbalance in the fisheries. An economic index, the RPI, decreased from 1994 to 2007, indicating that the values of lower trophic level (TL) species increased relative to those of higher TL species. Kajian ini telah dijalankan untuk mendapatkan anggaran indeks biologi dan ekonomi untuk struktur trofik penangkapan ikan Omani, iaitu aras trofik min (MLT), indeks penangkapan ikan yang seimbang (FiB) dan indeks harga relatif (RPI). Secara umumnya, MLT telah berkurangan dari 1995 hingga 2010, menunjukkan penangkapan ikan menurun dalam web trofik marin. Indeks FiB telah meningkat, menunjukkan ketidakseimbangan dalam perikanan. Indeks ekonomi, RPI telah menurun dari 1994 hingga 2007, menunjukkan bahawa nilai spesies aras trofik (TL) bawah telah meningkat secara relatif kepada spesies TL atas.